Mirror, mirror on the wall, are we ready for Gen-Z in marketplace? a study of smart retailing technology in Malaysia - Ng, Siew Imm; Ho, Jo Ann; Lim, Xin Jean; Chong, Kee Lin; Latiff, Khairunnisak (Emerald Publishing Limited, 2021)
Purpose : In this digitalization age, smart technologies are on the cusp of changing all business sector including retailing. Today’s consumers desire to shop in a smart store where the physical products on display are connected to the internet world. This study aims to propose a model for investigating Generation Z (Gen-Z) consumers’ expectations towards the smart retail technology (SRT) in the Malaysian context through the application of the stimulus-organism-response framework. Design/methodology/approach : By using a purposive sampling technique, a self-administered questionnaire was conducted. A total of 220 usable responses were collected from Gen-Z consumers who had experience in using SRT. The data were analysed using partial least square structural equation modelling (PLS-SEM). Findings : This study underscores the role of perceived usefulness, perceived enjoyment and perceived value on Gen-Z consumers’ attitude and word-of-mouth (WOM). Expectations on usefulness, enjoyment and value provide some ideas on Gen-Z consumers’ value who put a high emphasis on functional value, fun value and value for money when adopting the SRT. On the other hand, the result also demonstrates the mediating role of consumers’ attitude in connecting perceived value and perceived enjoyment on WOM towards SRT. Practical implications : The findings of this study provide beneficial insights for a retailer who desire to pursue a smart-related acquisition strategy. Retailers are recommended to embrace on the following three key features: innovative solution (high usefulness), reliable benefits (high perceived value) and fun experience (high enjoyment) to provide Gen-Z consumers with compelling experiences. Additionally, retailers are suggested to acknowledge the importance of managing consumers’ attitude in driving positive WOM evaluations. Originality/value : This paper responds to Ting et al.’s (2018) call in uncovering values and lifestyles of generation in details. In Malaysia, retailers ought to incorporate of the high level of usefulness, value and enjoyment when designing their SRT to constitute the Gen-Z consumers’ expectations. Moreover, similar to Ting’s conclusion, this cohort members are very much into technologies and they tend to embrace SRT in their lifestyles.